BMSC-Derived Exosomes Ameliorate Osteoarthritis by Inhibiting Pyroptosis of Cartilage via Delivering miR-326 Targeting HDAC3 and STAT1//NF-κB p65 to Chondrocytes - Honggang Xu; Bin Xu (Mediators of Inflammation)
Background. In the past decade, mesenchymal stem cells (MSCs) have been widely used for the treatment of osteoarthritis (OA), and noncoding RNAs in exosomes may play a major role. Aim. The present study is aimed at exploring the effect and mechanism of miR-326 in exosomes secreted by bone marrow mesenchymal stem cells (BMSCs) on pyroptosis of cartilage and OA improvement. Methods. Exosomes from BMSCs (BMSC-Exos) were isolated and identified to incubate with OA chondrocytes. Proliferation, migration, specific gene and miR-326 expression, and pyroptosis of chondrocytes were detected. BMSCs or chondrocytes were transfected with miR-326 mimics or inhibitors to investigate the effect of miR-326 in BMSC-Exos on pyroptosis of chondrocytes and the potential mechanism. Finally, a rat OA model was established to verify the effect and mechanism of miR-326 in BMSC-Exos on cartilage of pyroptosis. Results. Incubation with BMSC-Exos could significantly improve the survival rate, migration ability, and chondrocyte-specific genes (COL2A1, SOX9, Agg, and Prg4) and miR-326 expression of OA chondrocytes and significantly inhibit pyroptosis of chondrocytes by downregulation of the levels of inflammatory cytokines, Caspase-1 activity, and pyroptosis-related proteins such as GSDMD, NLRP3, ASC, IL-1β, and IL-18 (P<0.01). PKH26 labeling confirmed the uptake of BMSC-Exos by chondrocytes. Incubation with exosomes extracted from BMSCs overexpressing miR-326 can significantly repress the pyroptosis of chondrocytes, while knockdown of miR-326 had the opposite effect (P<0.01). The same result was also demonstrated by direct interference with the expression level of miR-326 in chondrocytes (P<0.01). In addition, we found that the overexpression of miR-326 significantly inhibited the expression of HDAC3 and NF-κB p65 and significantly promoted the expression of STAT1, acetylated STAT1, and acetylated NF-κB p65 in chondrocytes (P<0.01). The targeted relationship between miR-326 and HDAC3 was verified by dual-luciferase reporter assay. Animal experiments confirmed the mechanism by which miR-326 delivered by BMSC-Exos inhibits pyroptosis of cartilage by targeting HDAC3 and STAT1/NF-κB p65 signaling pathway. Conclusion. BMSC-Exos can deliver miR-326 to chondrocytes and cartilage and improve OA by targeting HDAC3 and STAT1//NF-κB p65 to inhibit pyroptosis of chondrocytes and cartilage. Our findings provide a new mechanism for BMSC-Exos to treat OA.